The Role of Games and Their Significance at Different Levels of Learning Foreign Languages - Farida Azamovna Pulatova (Periodica Journal, 2023)
This article discusses the importance of role-playing games and the possibilities of their use in teaching foreign languages. In the course of the lesson, the criteria for using role-playing games and the main value of giving the student the necessary skills that can be used in real communication are shown
Keywords: communication; role play; speech